2017
DOI: 10.1016/j.ijpharm.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Spray drying of poorly soluble drugs from aqueous arginine solution

Abstract: Co-amorphous drug-amino acid mixtures have shown potential for improving the solid-state stability and dissolution behavior of amorphous drugs. In previous studies, however these mixtures have been produced mainly with small-scale preparation methods, or with methods that have required the use of organic solvents or other dissolution enhancers. In the present study, co-amorphous ibuprofen-arginine and indomethacin-arginine mixtures were spray dried from water. The mixtures were prepared at two drug-arginine mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 48 publications
3
27
2
2
Order By: Relevance
“…Instead, Trc was not observed for GBC-ARG. The single Tg value observed was found to be lower than for pure GBC and higher than that previously estimated for ARG (18.4°C [41], 34.0°C [32] and 55°C [53]). When SLS was added to the mixture, the value of Tg was lowered somewhat further.…”
Section: Differential Scanning Calorimetry Measurementscontrasting
confidence: 76%
See 3 more Smart Citations
“…Instead, Trc was not observed for GBC-ARG. The single Tg value observed was found to be lower than for pure GBC and higher than that previously estimated for ARG (18.4°C [41], 34.0°C [32] and 55°C [53]). When SLS was added to the mixture, the value of Tg was lowered somewhat further.…”
Section: Differential Scanning Calorimetry Measurementscontrasting
confidence: 76%
“…Additionally, amorphous ARG salts have been prepared with several drug molecules, and similar changes in the IR peaks of ARG between the spectra of amorphous salts and amorphous ARG (i.e. shifts in the C-N stretching, COOstretching and aliphatic chain vibrations) have been observed previously [32,[40][41][42][43][44][45]. Thus, in addition to salt formation, also hydrogen bonding between GBC and ARG [46,47] as well as an interaction between the guanidinium group of ARG (vibrations at 1674 cm -1 and 1614 cm -1 in crystalline ARG) and the aromatic moiety of GBC [41,46,48,49] should be considered as a possible source for the changes in the IR spectrum of the co-amorphous GBC-ARG mixture.…”
Section: Sersupporting
confidence: 58%
See 2 more Smart Citations
“…For other molar ratios, it has been observed that the co-amorphous SDs recrystallize to pure components, with the excess component crystallizing faster [ 15 , 19 ], unless other mechanisms are involved [ 24 ]. However, there have also been studies [ 35 , 55 ] showing stability for other molecular proportions. For example, 2:1, 1:1 and 1:2 compositions of tranilast-diphenhydramine systems remained amorphous during 30 days and 1: 1 and 1:2 co-amorphous dispersions of IBU-ARG and IND-ARG did not crystallize, probably due to hydrogen bonding along with salt formation, which can explain the high stability of the 1:2 composition.…”
Section: Co-amorphous Dispersionsmentioning
confidence: 99%